2010
DOI: 10.1111/j.1461-9563.2010.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Local and landscape effects on bee communities of Hungarian winter cereal fields

Abstract: 1 Pollination is a key ecosystem service. Although bees are the most important pollinators, they are endangered by intensive agricultural practices. The present study investigated the effects of farmland management and environmental factors at local and landscape scales on bees in Central Hungary. 2 Bees were sampled in winter cereal fields that varied in the amount of applied fertilizer and insecticide use. Measurements included total, small and large bee species richness and abundance; stability of total spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 45 publications
2
31
0
1
Order By: Relevance
“…Interestingly, the pan traps attracted similar numbers of bees in both seasons, whereas the vane traps, which should not lose insects due to splashing, were less effective in the rainy season. To put the numbers into perspective, a study from central Hungary collected on average 2.8 bees per day in their yellow pan traps placed in winter cereal fields during six weeks in May and June, and blue vane traps attracted between 0.33 and 3.44 bees per hour, in the Zumwalt Prairie Preserve in Oregon, U.S.A. (Kovacs-Hostyanszki et al, 2011;Kimoto et al, 2012), which is more than 70 times higher than we sampled during the rainy season. Studies from Europe and North America have found that pan traps may undersample some species groups and also large bodied species, but on the other hand be very effective in sampling small bees (Westphal et al, 2008;Wilson et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the pan traps attracted similar numbers of bees in both seasons, whereas the vane traps, which should not lose insects due to splashing, were less effective in the rainy season. To put the numbers into perspective, a study from central Hungary collected on average 2.8 bees per day in their yellow pan traps placed in winter cereal fields during six weeks in May and June, and blue vane traps attracted between 0.33 and 3.44 bees per hour, in the Zumwalt Prairie Preserve in Oregon, U.S.A. (Kovacs-Hostyanszki et al, 2011;Kimoto et al, 2012), which is more than 70 times higher than we sampled during the rainy season. Studies from Europe and North America have found that pan traps may undersample some species groups and also large bodied species, but on the other hand be very effective in sampling small bees (Westphal et al, 2008;Wilson et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The pan traps placed in the hedgerow and in the adjacent wheat field in different distances from the hedge showed higher species richness and abundance of hoverflies in 10 m in the wheat field than along the hedge. White pan traps have visually alluring effect on insects in the wheat field, especially in the absence of flowers (Sobota & Twardowski 2004;Sarthou et al 2005;Kovács-Hostyánszki et al 2011). But more probably the shady habitat inside the hedgerow caused by the closed canopy is not preferable for hoverflies (Röder 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This may seem a contra-intuitive finding, however, we think it is explainable by the high foraging ranges of bumblebees. Kovács-Hostyánszki et al (2011), also in Hungary, found that the percentage of semi-natural habitats in a 500 m radius did not influence bee species richness and abundance of bumblebees. According to Heard et al (2007) bumblebee densities were higher locally if the patch was more profitable, but, controlling for that, densities did not vary with patch size, i.e.…”
mentioning
confidence: 87%
“…Particularly the loss of flower-rich, semi-natural landscape elements in farmland, such as field margins, diverse meadows and arable weeds in crops contribute to this process , Tscharntke et al 2005. At field level, the increase in the amount of fertilizers applied to arable fields led to a strong decline in species diversity and flower richness within the managed fields (Kleijn et al 2009, Kovács-Hostyánszki et al 2011) and in semi-natural habitats adjacent to fertilized fields (Bakker & Berendse 1999). Thus, flower rich natural habitats are crucial for the preservation of bumblebee populations at various scales.…”
Section: Introductionmentioning
confidence: 99%